Low-temperature performance of GeSn-on-Si avalanche photodiodes toward single-photon detection - Wanitzek, Maurice; Hack, Michael; Schwarz, Daniel; Schulze, Jörg; Oehme, Michael (Materials Science in Semiconductor Processing, 2024)
Avalanche photodiodes utilizing GeSn as an absorbing material can be used for low-light detection of telecommunication wavelengths, such as 1550 nm. We present the performance of GeSn-on-Si avalanche photodiodes at low-temperatures down to 110 K. It was found, that at temperatures above 190 K the dark current is dominated by generation-recombination due to trap states at the SiO2-semiconductor interface with an activation energy of ∼0.2 eV. At lower temperatures and high reverse voltages the leakage mechanism shifts to trap-assisted-tunneling. Responsivity measurements show the shift of the absorption edge toward shorter wavelengths. For 1550 nm and at 140 K a responsivity of 0.097 A/W is achieved, which is five times higher than a Ge reference-APD. When biased in the Geiger-mode, measurements of the dark count rates were performed, marking the first step towards GeSn-on-Si single-photon detectors for 1550 nm radiation.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Avalanche photodiode; Dark current; Geiger-mode; Germanium–tin; Infrared; Quantum application